Meteotsunamis: atmospherically induced destructive ocean waves in the tsunami frequency band - S. Monserrat; S. Monserrat; I. Vilibić; A. B. Rabinovich; A. B. Rabinovich (Natural Hazards and Earth System Sciences, 2006)
In light of the recent enhanced activity in the study of tsunami waves and their source mechanisms, we consider tsunami-like waves that are induced by atmospheric processes rather than by seismic sources. These waves are mainly associated with atmospheric gravity waves, pressure jumps, frontal passages, squalls and other types of atmospheric disturbances, which normally generate barotropic ocean waves in the open ocean and amplify them near the coast through specific resonance mechanisms (Proudman, Greenspan, shelf, harbour). The main purpose of the present study is to describe this hazardous phenomenon, to show similarities and differences between seismic and meteorological tsunamis and to provide an overview of meteorological tsunamis in the World Ocean. It is shown that tsunamis and meteotsunamis have the same periods, same spatial scales, similar physical properties and affect the coast in a comparably destructive way. Some specific features of meteotsunamis make them akin to landslide-generated tsunamis. The generation efficiency of both phenomena depend on the Froude number (Fr), with resonance taking place when Fr~1.0. Meteotsunamis are much less energetic than seismic tsunamis and that is why they are always local, while seismic tsunamis can have globally destructive effects. Destructive meteotsunamis are always the result of a combination of several resonant factors; the low probability of such a combination is the main reason why major meteotsunamis are infrequent and observed only at some specific locations in the ocean.